(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article highlights the strategic place granted by the 2006 reform in Argentina to the Artistic Area and reflects on the link between theater pedagogy and educational reforms. In the first place, the three central educational purposes are proposed: citizen training, training for the world of work and training in the field of culture, focusing on those related to Art Education. Second, Theater is presented as a curricular subject and three central axes are made explicit: elements of theatrical language, artistic theatrical production and social and historical contextualization of artistic manifestations. Finally, the conception of Art is linked to the pedagogical approach of Theater as a curricular subject.